2021
DOI: 10.3390/ijerph18126334
|View full text |Cite
|
Sign up to set email alerts
|

Deploying a Fotonovela to Combat Methamphetamine Abuse among South Africans with Varying Levels of Health Literacy

Abstract: Poor health literacy in the Western Cape Province of South Africa is one of the main factors hampering methamphetamine (MA) use prevention efforts in the area, where the abuse of this drug is a major health and social problem affecting especially previously disadvantaged communities. In the first part of a two-part study, we compared a health-related fotonovela about MA to an existing brochure group and a control group. Main findings show that the vast majority of readers preferred the fotonovela over the exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…We also found that readers of the fotonovelas scored significantly more positively on attitudes towards speaking to a doctor or a nurse about diabetes, compared to the control condition. This finding is of interest, given the relevance of conversations about health messages to changes in beliefs, attitudes and behavioural intentions and ultimately behavioural change (Davis and Jansen, 2021).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…We also found that readers of the fotonovelas scored significantly more positively on attitudes towards speaking to a doctor or a nurse about diabetes, compared to the control condition. This finding is of interest, given the relevance of conversations about health messages to changes in beliefs, attitudes and behavioural intentions and ultimately behavioural change (Davis and Jansen, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…We measured attitudes towards starting conversations about diabetes. A meta-analysis by Jeong and Bae (2017) on the effects of campaign-generated conversations concluded that such conversations have a positive, albeit small, effect on inducing campaign-related outcomes (see also Davis and Jansen, 2021). Both attitudes (‘To speak to a doctor or a nurse about my risk for diabetes, is something I .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation